Growth and nutrition of Pitombeira (Tasilia esculenta Radlk) seedlings in different substrates and biofertilizer application - Cavalcante, Adailza Guilherme [UNESP]; Cavalcante, Alian Cássio Pereira; Souto, Antônio Gustavo de Luna; Zuza, José Flavio Cardoso; Dantas, Murielle Magda Medeiros; Araújo, Raunira Costa (Southern Cross Publishing, 2019)
The pitombeira (Tasilia esculenta Radlk.) is a fruit native to Brazil, which is being exploited in an extractive way. To get agronomic information, such as the formation of mudase to be used in future commercial plantations, therefore, the objective was to evaluate the initial development and accumulation of nutrients in pitombeira seedlings submitted to different organic substrates and biofertilizer application in the soil. The experimental design was in randomized blocks, with a factorial arrangement of 4 × 2 and five replications. The treatments corresponded to four substrates (W, control; CS, commercial substrate; RFV, composite of fruit and vegetable remnants of a university restaurant; SIP, residues of industrialized products) in the substrate without and with Supermagro biofertilizer. Ninety days after sowing, the plant height, stem diameter, total dry mass, Dickson Quality Index, and leaf content in macronutrients were evaluated. The use of residues of fruits and vegetables (RFV) and residues of industrialized products (SIP) is recommended for the composition of submetry of pitombeira because these contribute to the greater growth of pitombeira seedlings. The addition of organic residues increases the quality of pitombeira seedlings having higher quality as biofertilizer treatments. Commercial substrate (CS) increases nitrogen and potassium terrors for substrates with fruit and vegetable residues (RFV), and the residues of industrialized products (RPI) used for the propagation of pitombeira seedlings can be recommended for the production of seedlings, because they increase the leaf content of phosphorus, calcium, magnesium, and sulfur.
Keywords: Fruticulture; Leaf nutrients; Organic matter; Propagation; Talisia esculenta Radlk